2020
DOI: 10.1111/nph.16616
|View full text |Cite
|
Sign up to set email alerts
|

MRG1/2 histone methylation readers and HD2C histone deacetylase associate in repression of the florigen gene FT to set a proper flowering time in response to day‐length changes

Abstract: Summary Day‐length changes represent an important cue for modulating flowering time. In Arabidopsis, the expression of the florigen gene FLOWERING LOCUS T (FT) exhibits a 24‐h circadian rhythm under long‐day (LD) conditions. Here we focus on the chromatin‐based mechanism regarding the control of FT expression. We conducted co‐immunoprecipitation assays along with LC‐MS/MS analysis and identified HD2C histone deacetylase as the binding protein of the H3K4/H3K36 methylation reader MRG2. HD2C and MRG1/2 regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 43 publications
0
26
0
1
Order By: Relevance
“…Generally, histones are featured by their large quantity and various modification residues ( 46 , 58 ). At least eight modifications have been identified in histones, and these modifications are catalyzed by distinct enzymes ( 59 , 60 ).…”
Section: Histone Methylation In Cvd Progressionmentioning
confidence: 99%
“…Generally, histones are featured by their large quantity and various modification residues ( 46 , 58 ). At least eight modifications have been identified in histones, and these modifications are catalyzed by distinct enzymes ( 59 , 60 ).…”
Section: Histone Methylation In Cvd Progressionmentioning
confidence: 99%
“…FLOWERING LOCUS T (FT) is a origen gene that promotes owering in Arabidopsis under long-day conditions. Guo, et al (2020) studied the epigenetic regulation mechanism of the FT gene in Arabidopsis and reported that HD2C is recruited to the locus of FT at dusk via an MRG1/2 dependent pathway to regulate owering time under long-day conditions. HD2C binds with histone methylation readers MRG1/2 and deacetylates lysine 9, 23, 27 of histone H3 to repress FT gene expression and early owering.…”
Section: Evolution and Molecular Characteristics Of The Plant-speci C Hd2 Familymentioning
confidence: 99%
“…In plants, Arabidopsis encodes two homologs of human MRG15, MRG1 and MRG2, which bind to H3K4me3/H3K36m3modifying histone marks and trigger temperature-induced flowering via the florigen gene FT (Bu et al, 2014). However, it seems like that MRG1/2 have diversified from their animal homologs during evolution, yet they still maintain their conserved H3K36me3-binding molecular function (Xu et al, 2014;An et al, 2020;Guo et al, 2020). Recently, a protein complex in Arabidopsis, called anti-silencing 1 (ASI1)-ASI1 immunoprecipitated protein 1 (AIPP1)-enhanced downy mildew 2 (EDM2) (AAE) complex, was identified targeting genic heterochromatic elements to regulate APA (Duan et al, 2017).…”
Section: Histone Modification-mediated Regulation Of Alternative Rna mentioning
confidence: 99%